2007
DOI: 10.1007/s10875-007-9128-5
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the Expression of CD4 Isoforms in Oral Epithelia and Saliva from Patients with Oral Lichen Planus

Abstract: Oral lichen planus (OLP) is a chronic inflammatory mucosal disease that cell-mediated immunological mechanisms are involved in pathogenesis. The objective of this study was to investigate the expression of CD44 isoforms including CD44s, CD44v5, and CD44v6 in biopsy specimens and saliva from OLP patients. Thirty-one OLP patients and 30 healthy subjects were enrolled in this study. Immunohistochemical methods were used to detect the expression of CD44 isoforms in oral epithelia, and enzyme-linked immunosorbent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 59 publications
3
16
0
Order By: Relevance
“…Moreover, a significant difference was observed in the expression patterns of CD44v6, SYNE1, and miR34a in leukoplakia patients compared to their healthy counterparts, thereby suggestive of the role of these markers in early diagnosis and early risk prediction of OSCC using non‐invasive techniques. Our findings are in concordance with the results of Godge et al; however, they are in sharp contradiction with the work of Chaiyarit et al who found a significant reduction in the expression of CD44v6 in oral leukoplakia patients compared to controls. This discrepancy could be attributed to the difference in sample source and techniques employed.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, a significant difference was observed in the expression patterns of CD44v6, SYNE1, and miR34a in leukoplakia patients compared to their healthy counterparts, thereby suggestive of the role of these markers in early diagnosis and early risk prediction of OSCC using non‐invasive techniques. Our findings are in concordance with the results of Godge et al; however, they are in sharp contradiction with the work of Chaiyarit et al who found a significant reduction in the expression of CD44v6 in oral leukoplakia patients compared to controls. This discrepancy could be attributed to the difference in sample source and techniques employed.…”
Section: Discussionsupporting
confidence: 73%
“…Apparently, the lower expression of CD44 in group B compared to that in group A is because of the effects of inflammation. Several inflammatory cytokines, such as TNF α and IF γ , are said to be involved in regulation of CD44 expression – the role of which is also reported in OLP …”
Section: Discussionmentioning
confidence: 99%
“…CD44 is considered a main receptor for hyaluronan (HA) . Under physiological conditions, hyaluronan is usually found in the form of a high‐molecular‐weight (HMW) mass in ECM .…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological characteristics of OLP demonstrate inflammatory responses, such as intense subepithelial infiltration of T lymphocytes, degeneration of basal keratinocytes and epithelial basement membrane disruption (3, 4). Alterations in the biological functions of cells in the oral mucosal tissues of OLP have been investigated in different aspects such as alterations in pro‐inflammatory cytokines (5–8), recruitment of dendritic cells (9, 10), expression of various adhesion molecules (11–14) and oxidative and nitrative DNA damage in oral epithelia (15). Keratinocyte apoptosis (16, 17) and proliferation (18, 19) in patients with OLP have been reported.…”
Section: Introductionmentioning
confidence: 99%